Novel mutations in Vicugna pacos (alpaca) Tyrp1 are not correlated with brown fibre colour phenotypes - Feeley, Natasha; Bottomley, Steven; Munyard, Kylie (Elsevier BV, 2016)
© 2016 Elsevier B.V. The tyrosinase related protein 1 (Tyrp1) gene is a logical candidate to house the causative mutation for the brown fibre colour phenotype that exists in alpacas. Polymorphisms in Tyrp1 have been associated with brown fibre colour phenotypes in several species including mice, cows, cats and sheep. To investigate the role of Tyrp1 on coat colour variation in alpacas, the complete coding region of Tyrp1 was sequenced in a cohort of black and brown alpacas. Alpaca Tyrp1 is 1614 nucleotides long and encodes a 537 amino acid protein. Eleven novel polymorphisms were identified within the coding region, and eight within introns. Analysis of the only non-synonymous polymorphism showed no association with fibre colour (T262R; c.785C > G, p = 0.90). There was no association observed between any of the polymorphisms and fibre colour. An homology model of Tyrp1 suggests that the T262R mutation causes minimum disruption of structure. These results provide evidence for the absence of a eumelanic brown phenotype caused by Tyrp1 variants in the Australian alpaca population.